Resistive MHD modes in hollow cathodes external plasma. (25th January 2022) - Becatti, G; Burgalassi, F; Paganucci, F; Zuin, M; Goebel, D M
Abstract: A significant number of plasma instabilities occur in the region just outside of hollow cathodes, depending on the injected gas flow, the current level and the application of an external magnetic field. In particular, the presence of an axial magnetic field induces a helical mode, affecting all the plasma parameters and the total current transported by the plasma. To explore the onset and behavior of this helical mode, the fluctuations in the plasma parameters in the current-carrying plume outside of a hollow cathode discharge have been investigated. The hollow cathode was operated at a current of 25 A, and at variable levels of propellant flow rate and applied magnetic fields. Electromagnetic probes were used to measure the electromagnetic fluctuations, and correlation analysis between each of the probe signals provided spatial-temporal characterization of the generated waves. Time-averaged plasma parameters, such as plasma potential and ion energy distribution function, were also collected in the near-cathode plume region by means of scanning emissive probe and retarding potential analyzer. The results show that the helical mode exists in the cathode plume at sufficiently high applied magnetic field, and is characterized by the presence of a finite electromagnetic component in the axial direction, detectable at discharge currents ⩾25 A. A theoretical analysis of this mode reveals that one possible explanation is consistent with the hypotheses of resistive magnetohydrodynamics, which predicts the presence of helical modes in the forms of resistive kink. The analysis has been carried out by linear perturbation of the resistive MHD equations, from which it is possible to obtain the dispersion relation of the mode and find the k – ω unstable branch associated with the instability. These findings provided the basis for more detailed investigation of resistive MHD modes and their effect in the plume of hollow cathodes developed for electric propulsion application.